An Analysis of Intra-Lexical Code-Mixing on Podcast Youtube Channel - Adnyasuari, Ni Putu Diah; Putu Ayu Asty Senja Pratiwi; I Komang Sumaryana Putra (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2024)
Advances in technology and information in social media contribute to the use of an international language, namely English. In communicating, the younger generation of Indonesia is also exposed to using English. The title of this article namely, “An Analysis of Intra-Lexical Code-Mixing in Podcast YouTube Channel” discusses the code-mixing phenomenon. The goal of this research is to ascertain the types of Intra-Lexical and also the level of using code-mixing in AH podcast YouTube channels. Data was taken and collected from Atta Halilintar's Youtube channel account. Documentation and observation were the methods used to gather data. The writer uses qualitative-descriptive method Hoffman's (1991) theory is used to classify the Intra-Lexical code-mixing types and Suwito's (1988) theory to classify the types of code-mixing levels. For the data collection steps in this analysis used observation and note-taking techniques. The results found in this code-mixing research are that in AH podcast, 35 code-mixings used by participants were identified. The most dominant data in this research is the application of intra-lexical in code-mixing of suffix type, while the most dominant type of level used is word-level code-mixing.